Analysis of the charge state distribution in an ECRIS Ar plasma using high-resolution x-ray spectra - Guerra, Mauro António Moreira; Amaro, Pedro (Journal of physics. B, Atomic, molecular and optical physics, 2013)
In this work, we obtained a charge state distribution inside an Ar plasma produced by an electron-cyclotron-resonance ion source. The processes that lead to the observed lines in x-ray spectra are identified and included in the simulated x-ray spectrum. The geometrical constraints of the flat double crystal spectrometer, used to measure the x-ray spectrum, are investigated as they are crucial for correctly obtaining the ion densities from the observed transition amplitudes. Multiple electron impact ionization is included, and a realistic electron velocity distribution is taken into account. The charge state distribution of the Ar ions is compared to measured extracted ionic currents.
Gesehen am 11.02.2021